2020
DOI: 10.1128/aac.00086-20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ionophores Active against La Crosse Virus Identified through Rapid Antiviral Screening

Abstract: Bunyaviruses are significant human pathogens, causing diseases ranging from hemorrhagic fevers to encephalitis. Among these viruses, La Crosse virus (LACV), a member of the California serogroup, circulates in the eastern and midwestern United States. While LACV infection is often asymptomatic, dozens of cases of encephalitis are reported yearly. Unfortunately, no antivirals have been approved to treat LACV infection. Here, we developed a method to rapidly test potential antivirals against LACV infection. From … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
(33 reference statements)
0
21
0
2
Order By: Relevance
“…At the same time, National Institute for Viral Disease Control and Prevention, China CDC, Beijing, China, also revealed that VAL inhibited the replication of MERS-CoV with an EC 50 value of 6.07 μM and CC 50 value of 5.88 μM using an experimental design of dose–response studies in vitro [ 70 ]. Recently, it demonstrated that VAL exhibited inhibitory activity with an IC 50 value of 0.005 μM [ 71 ].…”
Section: Antiviral Activity Of Valinomycin Against Human Coronavirusementioning
confidence: 99%
See 4 more Smart Citations
“…At the same time, National Institute for Viral Disease Control and Prevention, China CDC, Beijing, China, also revealed that VAL inhibited the replication of MERS-CoV with an EC 50 value of 6.07 μM and CC 50 value of 5.88 μM using an experimental design of dose–response studies in vitro [ 70 ]. Recently, it demonstrated that VAL exhibited inhibitory activity with an IC 50 value of 0.005 μM [ 71 ].…”
Section: Antiviral Activity Of Valinomycin Against Human Coronavirusementioning
confidence: 99%
“…During the rapid antiviral screening to identify potential antivirals against the La Crosse virus, the VAL active against HCoV-229E infection was reported by Sandler et al. [ 71 ]. VAL showed inhibitory activity with an IC 50 value of 0.067 μM and exhibited a potent inhibitory against the replication of HCoV-229E at the concentration of 10 μM.…”
Section: Antiviral Activity Of Valinomycin Against Human Coronavirusementioning
confidence: 99%
See 3 more Smart Citations